The mediating role of Body Roundness Index in the association between Life’s Crucial 9 and infertility: a cross-sectional study using NHANES 2013–2018 - Wang, Ying; Gao, Lin; Zhong, Qianyi; Bao, Lingfen; Xu, Jianping; Zhang, Ling (Frontiers in Nutrition, 2025)
BackgroundRecent findings indicate a possible connection among heart health, obesity, and infertility. Yet, the processes through which obesity affects the link between heart health and infertility are still not well-understood. The newly created Life’s Crucial 9 (LC9) serves as a measure for evaluating heart health, and the Body Roundness Index (BRI) offers a more accurate and innovative approach to measuring central obesity. The objective of this research is to explore the link between LC9 and infertility and determine if BRI serves as an intermediary in this connection.MethodsThe data for this cross-sectional analysis was sourced from the 2013 to 2018 National Health and Nutrition Examination Survey (NHANES). Following the application of exclusion criteria, 2,319 women aged between 18 and 45 years were incorporated. To investigate the link between LC9, BRI, and infertility, methods like weighted multivariable logistic regression models, restricted cubic spline (RCS) analysis, and subgroup analyses were utilized. Furthermore, an analysis of mediation was performed to determine if BRI played a mediating role in the link between LC9 and infertility.ResultsWithin the demographic of the study, infertility occurred in 13% of cases. Post-adjustment for every covariate, a rise of 10 units in LC9 correlated with a 29% decrease in infertility rates (OR = 0.71, 95% CI: 0.61–0.84, P < 0.001). In contrast, a one-unit rise in BRI correlated with a 14% increase in infertility rates (OR = 1.14, 95% CI: 1.07–1.23, P < 0.001). Analysis using the RCS method revealed a direct negative relationship between LC9 and infertility, and a positive correlation between BRI and infertility. Mediation analysis showed that BRI mediated 16.26% of LC9’s overall impact on infertility (P < 0.001), suggesting a substantial influence of central obesity in this correlation.ConclusionThere is a significant negative correlation between LC9 and infertility, with BRI playing a partial mediating role. These findings highlight the importance of cardiovascular health and obesity management in reproductive health and suggest that reducing central obesity may lower the risk of infertility. Further research is needed on potential intervention strategies targeting metabolic and cardiovascular health to prevent infertility.